2022
DOI: 10.1155/2022/4955277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Periodontitis on Glycemic Control and Metabolic Status in Diabetes Patients: Current Knowledge on Early Disease Markers and Therapeutic Perspectives

Abstract: Diabetes mellitus and periodontitis are two of the most common chronic diseases affecting the world’s population, and they are intimately linked. For several years, in fact, it has been known that there is an interdependent relationship between the two diseases: Diabetes promotes the destruction of periodontal tissues, and periodontal disease negatively affects glycemic control. In relation to the control of dental plaque and oral dysbiosis responsible for periodontal disease, both nonsurgical and surgical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…This combination does not foretell the best outcomes for oral health, and it is likely/will likely be associated with a high edentulism experience [ 2 , 20 , 21 , 24 ]. In the present study, T2DM was a risk factor for edentulism as reported in other studies [ 8 , 9 , 21 , 34 , 36 ]. In recent years, the connection between oral health and systemic health has been widely recognized by the dental and medical professions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This combination does not foretell the best outcomes for oral health, and it is likely/will likely be associated with a high edentulism experience [ 2 , 20 , 21 , 24 ]. In the present study, T2DM was a risk factor for edentulism as reported in other studies [ 8 , 9 , 21 , 34 , 36 ]. In recent years, the connection between oral health and systemic health has been widely recognized by the dental and medical professions.…”
Section: Discussionsupporting
confidence: 88%
“…The bidirectional link between diabetes and periodontitis has been well established: through various mechanisms, diabetes promotes the destruction of periodontal tissues and periodontal disease negatively affects glycemic control [ 34 ]. The prevalence of edentulism in patients with T2DM is associated with oral problems such as salivary gland hypofunction, periodontitis, root caries, and pulpal involvement after severe carious lesions, as well as being associated with general health factors such as depression, cognitive impairment, and pain [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the treatment of periodontitis impacts metabolic control and reduction of systemic inflammation in patients with type 2 DM. 26,27…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, periodontitis is now known as a risk factor for worsening glycemic control and may increase the risk for diabetic complications (Nguyen et al, 2020;Santonocito et al, 2022).…”
Section: Discussionmentioning
confidence: 99%